PEACE JOURNALISM IN NEWS TOLIKARA RELIGION CONFLICT IN TEMPO.CO - JURNALISME DAMAI DALAM BERITA KONFLIK AGAMA TOLIKARA DI TEMPO.CO - Christiany Juditha (BPSDMP Kominfo Manado, 2016)
Conflicts that lead to violence between religious groups occurred in Tolikara, Papua in 2015. These events coincided during the celebration of Eid al-Fitr. Center for Religious and Cross-Cultural Studies (CRCS) UGM reported at the beginning of these events occur, the news appeared in the media in part still needs to be verified. Some are within the limitations of the information precisely to provoke further towards inter-religious conflict. Though the mass media should still need to implement the peace journalism in reporting. The purpose of this study was to obtain an overview of the implementation of the peace journalism in the news about religious conflict of Tolikara in Tempo.co. This study uses a quantitative content analysis. The results showed that most of the news published in Tempo.co orientation leads to peace. The majority of news highlights the root of the problem, as well as featuring many wise leaders outside the circle of conflict. Tempo.co are less likely to show the perpetrators of conflict, and the description of the conflict as a mirror losses for peace. Even for the source or the people who were directly involved in the conflict did not exist (community orientation). Opinion on the orientation of the truth is not found. While the orientation of the completion of the solutions offered relatively more. Keywords: Journalism peaceful, news, religious conflicts led, online media.Konflik yang mengarah pada kekerasan antar umat beragama terjadi di Kabupaten Tolikara, Papua pada 2015. Peristiwa ini bertepatan saat perayaan Hari Raya Idul Fitri. Center for Religious and Cross-Cultural Studies (CRCS) UGM melaporkan di awal peristiwa ini terjadi, berita-berita yang muncul di media massa sebagian masih perlu diverifikasi. Sebagian lagi dalam keterbatasan informasi justru melakukan provokasi lebih jauh terhadap konflik antar agama. Padahal semestinya media massa tetap harus menerapkan jurnalisme damai dalam pemberitaannya. Tujuan penelitian ini adalah untuk mendapatkan gambaran tentang penerapan jurnalisme damai dalam berita tentang konflik agama Tolikara di Tempo.co. Penelitian ini menggunakan metode analisis isi kuantitatif. Hasil penelitian menunjukkan sebagian besar berita yang dimuat di Tempo.co mengarah pada orientasi perdamaian. Mayoritas berita menonjolkan akar masalah, serta banyak menampilkan tokoh bijak di luar lingkaran konflik. Tempo.co cenderung kurang menampilkan pelaku konflik, serta gambaran kerugian konflik sebagai cermin untuk perdamaian. Bahkan untuk sumber atau orang-orang yang terlibat langsung dalam konflik sama sekali tidak ada (orientasi masyarakat). Opini pada orientasi kebenaran juga tidak ditemukan. Sedangkan orientasi penyelesaian solusi yang ditawarkan relatif lebih banyak.Kata kunci: Jurnalisme damai, berita, konfik agama, media online